Associated Factors with Premalignant and Malignant Diagnoses in Cutaneous Horns [Factores Asociados a Diagnósticos Premalignos y Malignos en Cuernos Cutáneos] - Fuenzalida-Cruz, H; Chavez-Rojas, F; Reeves-Varela, M (Ediciones Doyma, S.L., 2020)
Introduction: Cutaneous horn (CC) is a conical hyperkeratotic tumor lesion, the importance of which lies in the underlying pathology. Objectives: 1) To characterize the CC according to sex, age, anatomical location and histopathological diagnosis; 2) Evaluate the association of these variables with diagnoses of malignancy in CC. Methodology: Prospective longitudinal observational study, in subjects with a preoperative diagnosis of cutaneous horn, carried out in a dermatology service between January 2018 and December 2019. Age, sex, location and histopathological diagnosis were recorded. Statistical analysis performed using the Stata program (Stata/SE 16.0 for Windows). Results: 57 patients were included, with a median (RIC) age of 75 (19) years. 31 (54.3%) patients were men. The lesions in the photoexposed area were 47 (82.5%). The most common histopathological diagnosis was actinic keratosis (n = 20; 35%). Premalignant/malignant and benign histopathological diagnoses corresponded to 39 (68.4%) and 18 (31.5%), respectively. The age (median (IQR)) of subjects with a histopathological diagnosis of premalignant/malignant lesion (79 (18) years) was significantly higher than that of subjects with benign lesion (65.5 (14) years) (p < 0.01). The frequency of localization in photoexposed area in subjects with premalignant/malignant lesion versus benign lesion was 92.31% (36/39) versus 61% (11/18), respectively (p < 0.01). There was no significant difference for males in premalignant/malignant versus benign lesions. Conclusions: Precursor lesion of CC is of an uncertain nature, for which reason its removal is essential for histopathological study. Advanced age and chronic photoexposure are variables associated with premalignancy/malignancy in CC. © 2020